Ghana : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
This paper reviews trends in GDP and other macroeconomic variables since independence. It assesses the performance of the different sectors of the economy and expenditure categories. The paper identifies a number of products that could contribute to maintaining the high growth rate that nontraditional exports have experienced. The medium-term fiscal sustainability analysis provides a useful quantification of the impact of the shocks experienced on fiscal performance. Ghana's social insurance system, stock exchange, divestiture program, rural finance, and poverty are also discussed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet